Versatile Structures of α-Synuclein - Wang, Chuchu; Zhao, Chunyu; Li, Dan; Tian, Zhiqi; Lai, Ying; Diao, Jiajie; Liu, Cong (Frontiers in Molecular Neuroscience, 2016)
α-Synuclein (α-syn) is an intrinsically disordered protein abundantly distributed in presynaptic terminals. Aggregation of α-syn into Lewy bodies is a molecular hallmark of Parkinson’s disease (PD). α-Syn features an extreme conformational diversity, which adapts to different conditions and fulfills versatile functions. However, the molecular mechanism of α-syn transformation and the relation between different structural species and their functional and pathogenic roles in neuronal activities and PD remain unknown. In this mini-review, we summarize the recent discoveries of α-syn structures in the membrane-bound state, in cytosol, and in the amyloid state under physiological and pathological conditions. From the current knowledge on different structural species of α-syn, we intent to find a clue about about its function and toxicity in normal neurons and under disease conditions, which could shed light on the PD pathogenesis.